Water phase distribution and its dependence on internal structure in soaking maize kernels: a study using low-field nuclear magnetic resonance and X-ray micro-computed tomography - Wang, Baiyan; Gu, Shenghao; Wang, Juan; Wang, Guangtao; Guo, Xinyu; Zhao, Chunjiang (Frontiers in Plant Science, 2025)
IntroductionThe formation of yield and quality in maize involves the accumulation of substances such as starch, proteins, and fats, which interact with water within the kernel. Although temporal dynamics of grain moisture and its functional and environmental determinants have been broadly demonstrated, we still do not have a comprehensive understanding of the distribution of water phase within a kernel.MethodsWe investigated the relationship between tissue structural traits, including embryo volume (EMBV), endosperm volume (ENDV), vitreous endosperm volume (VEV), floury endosperm volume (FEV), and water content in different phases, such as bound water, semi-bound water, and free water, in maize kernels under different cultivars, nitrogen application rates, and soaking durations by combining low-field nuclear magnetic resonance (LF-NMR) and X-ray microcomputed tomography (μ-CT) for kernels.ResultsThe results demonstrate that bound water is the major phase (57-82%) in maize kernels, and this proportion decreases with prolonged soaking duration. The bound water content and semi-bound water content positively correlate to ENDV, VEV, and EMBV, whereas free water content correlates to ENDV, EMBV, and VEV in descending order of correlation coefficient. This indicates that water might penetrate the embryo through the pedicel and vitreous endosperm through the pericarp during soaking.DiscussionFinally, we suggested that the proportion of semi-bound water could be a robust indicator to predict moisture content in maize kernels. The study provides a preliminary understanding of the structural basis of water distribution in maize kernels, thereby opening up the potential for designing efficient production systems and breeding cultivars well-suited for mechanical harvesting.